Criminalizing violations of the principle of transparency in public procurement as a means to combat corruption - Bensalem, Djoudi (The International tax journal, 2025)
This article addresses the criminal justice framework established by the Algerian legislator to uphold the principle of transparency in public procurement. Transparency is regarded as a cornerstone in the fight against corruption and in ensuring fairness in public contracts. The study examines both substantive and procedural aspects of crimes that undermine transparency in the field of public procurement. The focus is placed on offenses that directly violate this principle, such as bribery in the context of public contracts or the receipt of commissions, which breach the duty of integrity. Other offenses include the granting of unjustified advantages in public procurement and the failure to disclose conflicts of interest. The article analyzes the legal elements of each offense, their manifestations, and legal consequences. It also outlines the punitive system applied to these crimes, presenting the main and supplementary penalties applicable to both natural and legal persons. In addition, it explores general provisions concerning aggravating and mitigating circumstances, exemptions, attempts, complicity, and the statute of limitations. Further, the article examines the procedural framework for crimes against transparency in public procurement.